Curriculum Of Islamic Education in The Context of Free Learning: A Critical Study - Mulianah, Baiq (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The study examines the integration of the Islamic Education Curriculum in the context of the Merdeka Learning curriculum applied in Indonesia. The Free Learning curriculum, launched by the Ministry of Education and Culture, aims to give freedom and flexibility to schools and teachers in designing learning that matches the needs and potential of students. In this study, we explore how the principles and values of Islamic education can be aligned with the Free Learning approach. The methodology used is the study of critical literature involving analysis of policy documents, textbooks, and scientific articles related to the Curriculum of Free Learning and Islamic Education. To facilitate the process of analysis of research data, in this study data analysis using content analysis. The results of the research show that, that an effective integration between the Islamic Education Curriculum and the Freedom of Learning curriculum requires close cooperation between government, schools, and the community. A holistic and inclusive approach can help ensure that students not only gain academic knowledge, but also develop a strong character in line with Islamic values.